Omeprazole Inhibits Acetylsalicylic Acid-Modified Histamine Stimulation of Acid Secretion in Rabbit Gastric Glands - Daniel T Brosseuk; Iain GM Cleator; Andrew J Rae; Gilbert Wankling (Canadian Journal of Gastroenterology)
The effects of misoprostol and omeprazole on basal-, histamine- and acetylsalicylic acid (ASA)-induced gastric acid secretion by isolated rabbit gastric glands were studied. The authors found that ASA at a concentration of 2.4×10-3 M significantly inhibited acid secretion in the isolated gastric glands to 65% of basal levels, and that ASA at a concentration of 2.4×l0-2 M significantly inhibited the histamine stimulation of acid secretion to 78% of maximal. Misoprostol inhibited acid secretion to 76% of basal acid secretion, while omeprazole inhibited secretion to 58% of basal values. Misoprostol inhibited the ASA-modified histamine stimulation to 82% of maximal stimulation. In contrast, omeprazole was able to inhibit the ASA-modified histamine stimulation to 48% of maximal. This omeprazole inhibition of secretagogue-induced acid production reduced acid secretion to levels below basal secretion, indicating that neither histamine nor ASA (at the concentrations used), alone or in combination, had any stimulatory effect in the presence of omeprazole. Misoprostol is the recommended drug of choice for prevention and treatment of nonsteroidal anti-inflammatory drug (NSAID)-induced gastrointestinal mucosal injury. In vitro results suggest that omeprazole appears to treat this condition more effectively if gastric acid secretion is a necessary prerequisite for NSAID-induced mucosal injury.